Develop a FTTH network management system using visual basic - Ng, Boon Chuan; Ab-Rahman, Mohammad Syuhaimi; Premadi, Aswir; Jumari, Kasmiran (2009)
This paper proposed an efficient network management software tool named Smart Access Network _ Testing,Analyzing and Database (SANTAD) for remote control, inservice transmission surveillance, centralized monitoring, and fault detection for fiber-to-the-home (FTTH) using Visual Basic programming. A virtual network is setup to operate the software tool from central office (CO) or remote point.This program is able to prevent and detect the occurrence of fault in network system through event identification against optical signal level, attenuation, and losses.SANTAD enable each status of transmission link to be displayed a single screen with capability to configure the attenuation and detect the failure simultaneously.